Do youth farmers benefit from participating in contract farming? Evidence from French beans youth farmers in Arusha, Tanzania - Marwa, M.E.; Manda, J. (Informa UK Limited, 2022)
Contract farming (CF) is often seen as a system that enhances production efficiency leading to increased agricultural productivity and improved farmer livelihoods. However, there is a conflict in the literature on its impact on young farmers who are involved in farming in Sub-Saharan Africa. This paper evaluates the impacts of CF on crop yield, crop and household income among the youth farmers involved in French bean farming in Tanzania using cross-sectional data of 273 households. The study employs an endogenous switching regression (ESR) model that accounts for observed and unobserved factors to estimate the impact of CF. Further, the propensity score matching (PSM) model is used to check the robustness of ESR results. The results indicate that 162 farmers had contracts and French bean yields and incomes significantly increased with CF. Specifically, the empirical results reveal that CF leads to a gain of 17%, 34% and 37.5% in the yield, crop income and household income. Participation and impact of contract farming differed according to different socio-economic/institutional variables, such as access to extension services.